Strengthening the Links of the Bean Value Chain in Northern Nicaragua. - Membreño, Blanca; Chavarría Salguera, Jimmy Antonio; Lanuza, Augusto; Padilla, Norman; Escoto, Silvio; Valdivia Lorente, Rodolfo Ramón; Vásquez Vásquez, Augusto César; López Fonseca, Ernesto Antonio; Morán, Elizabeth; Gutiérrez, Jaime; Castro Rivera, Nubia; Gutiérrez, Augusto; et al. (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA). This document systematizes the experience of strengthening the links of the bean value chain in northern Nicaragua, with the purpose of improving the competitiveness of the sector through coordination of all the actors involved. Moreover, this report gathers all the lessons learned by the Technical Bean Commission, comprising representatives of the program’s local partners: ASDENIC, Cáritas Estelí, Cáritas Matagalpa, and FIDER.